Formas sustentáveis de construção - Souza, Regina Alves de [UNESP]; Castro, Ana Maria [UNESP]; Agostinho, Caio Arena [UNESP]; Barbosa, Gabriel Lima [UNESP]; Gabriel, Camila Pires Cremasco [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The modification in the way of people life are associated with technological development and population growth that have been causing significant environmental impacts. Today's society, seeks to minimize these impacts, in order to maintain or reduce the causes of them. One of the ways found by our society to reduce these impacts are the sustainable alternative constructions, these methods seeking to use recycle materials, for example, PET bottles, tires and aluminum can, which in addition to help the environment, also helps to reduce the cost the construction of houses. This study had the goal to investigate some methods and other existed forms of sustainable buildings.

As modificações no modo de vida das pessoas associados ao desenvolvimento tecnológicos e o crescimento populacional, vem causando impactos significativos. A sociedade atual, busca minimizar esses impactos ambientais, tentando preservar ou diminuir as causas do mesmo. Um dos meios encontrados pela sociedade para tentar neutralizar esses impactos foram: as construções alternativas sustentáveis, que buscam utilizar materiais descartáveis como exemplo garrafas PET, pneus e latinhas de alumínio, que além disso ainda, ajuda na redução dos custos na construção das casas. Este trabalho, teve com proposta investigar alguns métodos e formas existentes de construções sustentáveis.
Keywords: Sustentabilidade; Reciclagem; Casa alternativa